2017
DOI: 10.1037/fam0000324
|View full text |Cite
|
Sign up to set email alerts
|

Communication moderates effects of residential mobility on relationship quality among ethnically diverse couples.

Abstract: Although interpersonal communication is a defining feature of committed relationships, the quality of couple communication has not proven to be a straightforward cause of relationship quality. At the same time, emerging models argue that external circumstances likely combine with communication to generate changes in relationship quality. We integrate these two ideas by proposing that communication does exert effects on changes in relationship quality, but primarily when couples encounter challenging situations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
(44 reference statements)
1
8
1
Order By: Relevance
“…Compared to middle- or high-income couples, low-income (LI) couples report a greater proportion of external stressors that stem from outside the relationship (e.g., employment and finances, transition to parenthood, lack of access to healthcare, death of a loved one; Jackson et al, 2016) and systemic inequality (e.g., discrimination, neighborhood safety; Cutrona et al, 2003). Furthermore, LI couples with greater environmental stressors are likely to face greater relationship difficulties (Nguyen et al, 2017). As a result, LI couples present to relationship interventions with lower levels of relationship satisfaction and relationship stability as well as more intense contextual stressors such as poorer perceived health and more infrequent full-time employment (Williamson et al, 2019).…”
Section: Known Moderators Of LI Interventionsmentioning
confidence: 99%
“…Compared to middle- or high-income couples, low-income (LI) couples report a greater proportion of external stressors that stem from outside the relationship (e.g., employment and finances, transition to parenthood, lack of access to healthcare, death of a loved one; Jackson et al, 2016) and systemic inequality (e.g., discrimination, neighborhood safety; Cutrona et al, 2003). Furthermore, LI couples with greater environmental stressors are likely to face greater relationship difficulties (Nguyen et al, 2017). As a result, LI couples present to relationship interventions with lower levels of relationship satisfaction and relationship stability as well as more intense contextual stressors such as poorer perceived health and more infrequent full-time employment (Williamson et al, 2019).…”
Section: Known Moderators Of LI Interventionsmentioning
confidence: 99%
“…Several stress‐process models (Falconier, Randall, & Bodenmann, 2017) posit that interpersonal processes may not be influential to overall relationship satisfaction until they are needed (e.g., Masten, 2001). Nguyen et al (2017), for instance, found that positive observational communication processes (e.g., expressions of warmth/support) were not associated with change in satisfaction until a stressor occurred. When spouses turn to their partner during times of stress and their needs are not met, these disappointments may seem more representative of the overall functioning of the relationship, resulting in frustration and eroding marital satisfaction (Neff & Karney, 2017).…”
Section: Patterns Of Marital Satisfaction In Socioeconomically Disadvantaged Relationshipsmentioning
confidence: 99%
“…Nonetheless, self-reported dyadic coping has been shown to attenuate the adverse effects of stress on verbal aggression (Bodenmann, Meuwly, Bradbury, Gmelch, & Ledermann, 2010) and the adverse effects of posttraumatic stress on relationship quality (Lambert, Hasbun, Engh, & Holzer, 2015). Studies using observational coding of behavior also indicate that the effects of couples' communication on relationship satisfaction are dependent on couples' socioeconomic risk (Ross, Karney, Nguyen, & Bradbury, 2019) and changes in their neighborhood environment (see Nguyen, Williamson, Karney, & Bradbury, 2017 for another paper using the same sample). Furthermore, to our knowledge no study has addressed whether the association between behavior and satisfaction is altered by fluctuations in spouses' stress or their level of chronic stress relative to other spouses.…”
mentioning
confidence: 99%